Upconversion optical/magnetic resonance imaging-guided small tumor detection and in vivo tri-modal bioimaging based on high-performance luminescent nanorods. (January 2017) - Xue, Zhenluan; Yi, Zhigao; Li, Xiaolong; Li, Youbin; Jiang, Mingyang; Liu, Hongrong; Zeng, Songjun
Abstract: In this work, we demonstrated multifunctional NaYbF4 : Tm 3+ /Gd 3+ upconversion (UC) nanorods (UCNRs) with near-infrared (NIR)-to-NIR emission and controlled phase and size for UC optical and T1 /T2 dual-weighted magnetic resonance (MR) imaging-guided small tumor detection and tri-modal bioimaging. Cell toxicity and post-injection histology results revealed that our designed UCNRs present low biotoxicity and good biocompatibility in living animals. Real-time tracking based on UCNRs in living mice demonstrated that the UCNRs were mainly accumulated in the reticuloendothelial system (RES) and excreted through the hepatic pathway. Additionally, the UCNRs exhibited high X-ray absorption coefficient and large K-edge value, resulting in efficient in vivo CT imaging. A new type of binary (Yb 3+ /Gd 3+ ) MR contrast agent for simultaneous T1 /T2 dual-weighted MR imaging was achieved by doping Gd 3+ into NaYbF4 host. Importantly, a small tumor (5 mm in diameter) could be detected in vivo by intravenously injecting UCNRs under UC optical and MR imaging modalities. Therefore, these multifunctional nanoprobes based on NaYbF4 :Tm 3+ /Gd 3+ UCNRs with remarkable NIR-to-NIR emission provide potential applications for tri-modal UC optical, CT, binary T1 /T2 MR imaging, and early-stage tumor detection in nanomedicine.